Kajian Visual Mengenai Tokoh Wayang Kulit Purwa Antareja Gaya Yogyakarta - Ramdhani, Muhammad Abdan; Albar, Deni (Fakultas Desain Universitas Komputer Indonesia, 2021)
Antareja is one of the figures in the world of puppetry in Indonesia. It is said that Antareja is a descendant of Sang Hyang Anantaboga (the snake god in Javanese belief) and the child of the marriage of Raden Bima (Pandava figure) to Dewi Nagagini. Although the background is the Mahabharata story, Antareja is a Javanese original figure and not in the Hindu version of the Mahabharata story. This research was conducted with a qualitative analysis method to find out how Antareja figures were created and the depiction of Antareja figures based on the visuals shown. From the research it can be concluded that the character of Antareja has a visual meaning in every form of puppet anatomy, both from the shape of the head, body shape, foot shape, color and clothing.